Fungal colonization of rice straw and palm press fibre in the rumen of cattle and buffalo - Ho, Y.W.; Abdullah, N.; Jalaludin, S. (1991)
Fungal colonization and development in rice straw and palm press fibre (mesocarp of oil palm fruit after the extraction of oil) were very similar in both cattle and buffalo. In both animal species, attachment to rice straw by rumen fungal zoospores was rapid, within 15 min of rumen incubation. At 6 h of rumen incubation, thin- and thick-walled tissues were colonized by fungal hyphae and by 24 h fungal colonization was extensive. Fungi were predominantly those with spherical and ovoid sporangia. Fusiform sporangia were in fewer numbers. Fungal colonization was also extensive at 48 and 72 h. The colonization and development of the fungi on the palm press fibre, both untreated and treated with ammonium hydroxide and ether, was slow. © 1991.